Implementasi Perpustakaan Digital dalam Melayani Globalisasi Pemustaka - Anshari, Muhamad Hafiz; Zulaikha, Sri Rohyanti (Cendekia Inovatif Dan Berbudaya, 2025)
The rapid development of information technology has changed the way libraries provide services to users. The globalization of library services requires libraries to adapt to digital technology to increase service efficiency and accessibility. This research method uses literature study. The research results show that the application of digital technology, such as web-based management systems and library applications, increases operational efficiency and makes information access easier for users. However, challenges such as budget limitations, low quality of human resources, and infrastructure problems still hinder the optimization of digital systems. However, opportunities to expand the reach of services and improve service quality are increasingly open with advances in information technology.